Empowering Physical Education Teachers through Movement Literacy Training Based on Table Tennis in Elementary Schools - Indra Safari; Dewi Susilawati; Entan Saptani (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2026)
This community service program aimed to empower elementary school Physical Education (PE) teachers by enhancing their competence in implementing movement literacy through table tennis. The issue addressed was the limited ability and confidence of teachers to integrate movement literacy into PE lessons due to lack of training, inadequate facilities, and constrained teaching schedules. To respond to this challenge, a Participatory Action Research (PAR) approach was employed, emphasizing active involvement of teachers in problem identification, program design, training, implementation, and evaluation. The program was carried out in Sumedang Regency, West Java, over three months and involved 50 PE teachers.The intervention was structured through the acronym AKTIF (Analysis, Collaboration, Training, Implementation, Feedback). Teachers participated in practical training on movement literacy concepts, basic table tennis techniques, and creative pedagogical strategies. Simulated teaching sessions with modified media (folding tables, wooden boards, and simple rackets) were conducted to overcome facility limitations. The results indicated significant improvements in teachers’ technical skills, creativity, and confidence in delivering table tennis-based learning. Furthermore, a professional learning community of PE teachers was established as a sustainability strategy.In conclusion, the program effectively bridged the gap between theoretical understanding and practical teaching, providing an adaptable model for empowering teachers and strengthening students’ movement literacy.